DEMAND ANALYSIS OF INDONESIAN PULPWOOD USING TRANSCENDENTAL LOGARITHMIC MODEL: A STUDY OF THE WORLD AND SELECTED ASIAN MARKETS - Gunawan Ganda Tua Petrus Simanjuntak; Chingyang Lin (Indonesian Journal of Forestry Research, 2017)
Indonesia’s pulpwood export has shown an increasing trend since 1990s. Along with Brazil, Canada, USA and Chile, Indonesia became one of  the top five pulpwood exporter countries in the world. Indonesia’s pulpwood was traded mainly to some Asian countries. This paper examines Indonesian pulpwood export demand during the period  1994-2014 using a Transcendental Logarithmic (TL) model with Seemingly  Unrelated Regression (SUR) estimation. Export data from the five top exporter countries in four different markets (China, Korea, Japan and the world) were analysed. The important findings are as follow: firstly, logarithmic income and second order logarithmic income significantly influence the Chinese and Korean markets. Secondly, in general, Indonesia’s own-prices are elastic and have negative signs (-2.308, -1.06 and -2.04 in the Korean, Japanese and the world markets, respectively). Thirdly, due to its positive sign of  crossprice elasticity and also positive signs of  income elasticity (1.002, 1.722 and 0.625 in the Chinese, Korean and the world markets, respectively), Indonesian pulpwood could be categorized as a substitute and normal goods. Lastly, regarding to negative and elastic Indonesia’s pulpwood own-prices, one possible policy that could be applied by the Government of  Indonesia (GoI) is giving a subsidy to reduce pulpwood price by 10%. Subsidy could be implemented by reducing tax and retribution such as property tax (Pajak Bumi dan Bangunan) and local retribution (Retribusi Daerah). By doing so, it would give more benefit in the Korean market compared with other markets. Indonesia’s share of  demand would increase from 0.28 to 0.31 with high rate of  return (>2). On the world markets, Indonesia’s share of  demand would increase from 0.08 to 0.1 with a return rate of  1.89. This study, therefore, suggests that a subsidy policy should be implemented for pulpwood industry in Indonesia.